2015
DOI: 10.1007/s10815-015-0612-1
|View full text |Cite
|
Sign up to set email alerts
|

What maintains the high intra-follicular estradiol concentration in pre-ovulatory follicles?

Abstract: Purpose The purpose of the study was to establish the mechanism by which the estrogen concentration difference between the follicular fluid and the serum is maintained. Methods We used dialysis membrane with a pore size of <3 KD to characterize the estrogen-binding capacity of the follicular fluid. We performed PCR, western blot, and ELISA on luteinized granulosa cells to determine if sex hormonebinding globulin (SHBG) is produced by granulosa cells, and finally we used affinity columns and mass spectrometry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…It is a product of granulosa cells and its secretion from granulosa cells to the FF increases with gonadotrophin stimulation and mirrors the follicular estrogen production. Furthermore, it was identified as the main estradiol binding protein in FF and the most predictive FF solute of oocyte quality and IVF outcome ( Bayasula et al , 2013 ; Bentov et al , 2016 ). In our analysis, FF samples showed a high concentration of HSPG2 that was not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is a product of granulosa cells and its secretion from granulosa cells to the FF increases with gonadotrophin stimulation and mirrors the follicular estrogen production. Furthermore, it was identified as the main estradiol binding protein in FF and the most predictive FF solute of oocyte quality and IVF outcome ( Bayasula et al , 2013 ; Bentov et al , 2016 ). In our analysis, FF samples showed a high concentration of HSPG2 that was not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Localized in the basement membrane, HSPG2 provides a barrier, which is both size- and charge-selective, and promotes cell adhesion, endothelial cell growth and regeneration. In the ovary, it has been identified as a major estrogen-binding protein in follicular fluid ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis in the follicle wall can mediate the rupture of pre-ovulation follicles and release mature oocytes [ 66 , 67 , 68 ]. Bentov et al found that proteolysis affects the estrogen concentration in follicles [ 69 ]. In addition, there is a link between proteolysis and estrogen receptor activation [ 70 ].…”
Section: Discussionmentioning
confidence: 99%